If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(-5)=-(Y-0)
We move all terms to the left:
-(-5)-(-(Y-0))=0
We add all the numbers together, and all the variables
-(-(+Y))-(-5)=0
We add all the numbers together, and all the variables
-(-(+Y))+5=0
We calculate terms in parentheses: -(-(+Y)), so:We add all the numbers together, and all the variables
-(+Y)
We get rid of parentheses
-Y
Back to the equation:
-(-Y)
-(-1Y)+5=0
We get rid of parentheses
1Y+5=0
We add all the numbers together, and all the variables
Y+5=0
We move all terms containing Y to the left, all other terms to the right
Y=-5
| 817x=34 | | 4y-(y-4)=-2” | | 2g+5/2=2(g+5) | | v+8÷-3=6 | | 2x+6(4x+3)=2(6+4)-2 | | -4x+5=-1-3x | | (n=3)/5=-10 | | 2+2x–8=7x+5–5x | | 7(-x-11)+4=2(x-10)-161 | | 2(x-5)+3=9 | | 4(x-5)=2(2x-7)+6 | | 2(x–2)=50 | | Y-(-2)=-(x-4) | | 5y–1=5y+1 | | 7x+30=4x+7=180 | | 9.15=y+5 | | 3(x-4)+2(x+1)=5x-11 | | 4e+24=4X10^24 | | 4+8h=9h−6 | | y=-125+600 | | 3x+14+122.5=180 | | 5-2/3x=1/2x+-4 | | 7=c+37/7 | | -1r=-225 | | 15(2(x-1)=15(2(x+1) | | 24.7=y/12 | | 8x-6=2(x-3)+6 | | 4x−3=2x+7 | | 15u=6u+81 | | 26=12x | | Y-4=x-7 | | 2+a/4=-1+7 |